Optimization Model of Marketing Distribution Fish Processed Products by Transportation Method - Harsuko Riniwati; Lina Asmarawati; Eko Waluyo; Mentari Puspa Wardani; Dwi Sofiati (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2020)
The transportation model is a variation of a linear program developed specifically to problems solve related to transportation and the distribution of products from various sources to various destinations. The goal of transportation problems is to allocate goods at the source that all needs are met at the destination of the demand location. The purpose of this study is to analyze the allocation of the delivery of processed catfish products in POKLAHSAR Kediri Regency from the processing location to the market destination with the minimum allocation of marketing costs. The data were obtained from the catfish product processing group in Kediri Regency. Data were analyzed using the transportation optimization method model. The results of the analysis show that all factory capacities can meet the demands of all markets. There is not a single market that is not fulfilled. Suggestions for the research that the maximum profit can be achieved is the allocation of factory 1 product shipments to Tulungagung 165 packs and Ponorogo 65 packs. Factory 2 sent 220 packs to Ponorogo, Surabaya 50 packs, Jakarta 130 packs. Factory 3 sent to Tulungagung 50 packs. Factory 4 sends 100 packs to Ponorogo with a total minimum cost of IDR 620,000.